Variability and character association in heliconiya (heliconia spp) - Narkar Nikhil Dileep (Department of pomology and floriculture, College of Agriculture, 2012)
Heliconia cultivation is rapidly expanding in tropical areas throughout the world. Heliconia is one of the most important cut flower and landscape plants due to their variation in growth habit and flower characters combined with easy cultivation practices. India has great potential for expanding the cultivation of heliconia considering the rich and diverse germplasm of the crop available with us. The objective of the present study was to assess the extent of variability among the 30 selected species and cultivars. The study also was aimed at the evaluation of morphological and floral variability that exist in heliconia which will serve as a tool for identifying the varieties for further breeding programmes and to exploit the ornamental attributes of Heliconia for the expanding tropical cut flower industry in Kerala There was wide variation in morphological characters such as plant height, plant spread, number of leaves, leaf area and number of shoots and in flowering characters such as length of spike, length of petiole, length of inflorescence, number of flower bracts, number of flowers per bract, size of bract, days taken for flowering and flowering duration. Variation was also observed in pollen size and pollen fertility. Cultivar Heliconia chartacea cv. Sexy Pink registered the highest plant height and also the highest value for plant spread, leaf area, and length of inflorescence, days taken for flowering and flowering duration. However it recorded lower value for number of flowering shoots. Psittacorum species and interspecific hybrids recorded lower value for plant height, plant spread, leaf area, length of inflorescence, flowering duration and less number of days taken for first flowering but highest value for number of flowering shoots compared to heliconias which are having robust growth habit such as cultivar Pedro Ortiz, Jacquinii, wagneriana and stricta species. Interspecific hybrids recorded lower fertility percentage and other species and cultivars recorded higher fertility. Pollen shape varied within same species in different cultivars.